Estudo dos mecanismos de resistência e virulência de isolados de Cryptococcus neoformans e Cryptococcus gattii e quantificação de genes de bomba de efluxo pós tratamento com Galatos de Alquila - Rossi, Suélen Andreia [UNESP] (2014)
The increase of invasive mycoses and the development of antifungal resistance by some fungi species have been worrying. The antifungal treatment is usually aggressive and inefficient, and the emergence of antifungal resistance increases the difficulties in treating these fungi infections.Cryptococcus neoformans e Cryptococcus gattii are the main etiologic agents of cryptococcosis andespecially affect immunocompromised patients. In this work the Galleria mellonella, was used to perform the morphologic characterization as well as determine the virulence of three sequential clinical isolates of C. neoformansand twoisolates environmental of C. gattii. In addition, was held the analysis of genes expressions (MDR1, ERG11 and AFR1), that are involved in efflux pumps and ergosterol synthesis, by real time PCR (polimerase chain reaction) assay. After these characterizations the isolates were used in the prospecting of synthetic molecules to verify the inhibitory activity of selected genes. After incubation in vitro with fluconazole the C.neoformans isolates were classified as sensitive (26S), intermediate sensitivity (27I) and resistant (30R), and the C. gattiiisolates were resistant (118R) and the other sensitive (LC). The galic acid molecules and their synthetic derivatives were tests against C.neoformans and C. gattii isolates.The best results were obtained from alkyl gallates G11, G12, G14, G15, G16 and G17 which shows a great antifungal activity, especially G14, G16 e G17. The gallate n-dodecyl (G16), was select to others tests once presented additive activity in synergism test with fluconazole, decreasing the MIC values. The gene expression assay shows that both isolates expressed MDR1 and AFR1 (encoding efflux pumps), and the G16 was capable to inhibit these genes which makes this molecule promising for inhibiting efflux. With virulence assays using the G. mellonella was possible ...